Character Building of Students with Wise Use of Gadgets through Group Guidance Services - Wijayanah, Ade; Tobing, Christine Masada Hirashita; Saefudin, Dery Purnama (Journal of Counseling and Educational Research, 2025)
The purpose of the study is to "Formation of Student Character with Wise Use of Gadgets Through Group Guidance Services". The research method used is a quantitative approach. The population and sample in this study were students of class VII of SMP Bina Dharma, the population was 202 people and the sample was 53 students. Data were analyzed using SPSS software version 25. with the Kolmogorov-Smirnov Test normality test technique, which shows that the data is normally distributed (sig value > 0.05). To test the hypothesis, paired samples t-test is used. The results of the hypothesis test show a sig value (2-tailed) of 0.000, which is smaller than 0.05, so H0 is rejected and Ha is accepted. with the technique. The results of the study concluded in general that group guidance is effective for character formation with the use of gadgets. The results of this study are useful for schools in designing group guidance programs to be more effective in helping to improve student character formation and eradicate student problems.